ANALISIS FAKTOR-FAKTOR PROFITABILITAS PERUSAHAAN MENGGUNAKAN PURPOSIVE SAMPLING DAN REGRESI BERGANDA - Erni Puji Astuti (Jurnal Riset Akuntansi Terpadu, 2016)
Abstract The aim of this research is to analyze the influence of working capital management to manufacturing company. The sample which is used are the secondary data which is taken from the financial report of the manufacture firm in BEI since 2006-2010. The sample is taken with purposive method and which fufill the criteria of chossing sampling. The sample which is used are 27 firms. The analysis method which is used in this research is double regression. The result show that there are seven variables: net trade cycle, debt ratio, current ratio, inventory turn over in days, average payment period, cash conversion cycle, natural logarithm of sales which have significant effect on profitability. While variable average collection periods have no significant impact on profitability. Key words             :  Capital management, manufacturing company, profitability, purposive sampling, double regression. Abstrak Tujuan penelitian ini adalah untuk menganalisis pengaruh manajemen modal kerja terhadap perusahaan manufaktur. Data yang digunakan merupakan data sekunder yang diambil dari laporan keuangan perusahaan manufaktur yang terdapat di BEI selama tahun 2006-2010. Sampel diambil dengan metode purposive sampling, dan yang memenuhi kriteria pemilihan sampel. Sampel yang digunakan sebanyak 27 perusahaan. Metode analisis yang digunakan pada penelitian ini adalah regresi berganda. Hasil penelitian menunjukkan bahwa ada 7 variabel yaitu net trade cycle, debt ratio, current ratio, inventory turn over in days, average payment period, cash conversion cycle dan natural logarithm of sales yang berpengaruh signifikan terhadap profitabilitas. Sedangkan variabel average collection periods tidak berpengaruh signifikan terhadap profitabilitas. Kata Kunci      :  manajemen modal, perusahaan manufaktur, profitabilitas, purposive sampling, regresi berganda.